(untitled) (Journal of Imam Al-Kadhim College, 2024)
The phenomenon of fear was repeated in the poetic output of our research, and was manifested by two motives: fear of poverty and fear of authority. Therefore, the research was divided into three sections: the first: the first: “The concept of fear and a brief overview of the lives of the two poets,” the second: “Motives of fear in the two poets,” and the third: “The effect of fear on the artistic characteristics of the two poets.” Among its results: Their praise of the caliph was motivated by fear of his sword and a request for forgiveness for their people. By balancing their texts, We find that Al-Nimri is more fearful than Al-Atabi, as Al-Atabi summarized his poem, so it was planned with thought and woven with a method using rational logic and verbal argumentation, so it aroused the admiration of rhetoricians more than it aroused Al-Rashid, while Al-Nimri’s poems aroused Al-Rashid because he touched on a political topic, so the situation required elaboration in the introduction, praise and conclusion, with rhetorical embellishments, poetic idea and method, so Al-Nimri became the poet of the Caliph, while Al-Atabi’s poetry became a measure for poets to enter the Caliph and the princes, and it is no wonder that Al-Atabi preceded his student Al-Nimri and his narrator from whom he took, and from whose sea he drew, and in whose doctrine he resembled, and we did not find poetry by Al-Nimri motivated by fear of poverty, while we found poetry by Al-Atabi that was disturbed; Between contentment in life, and complaining about poverty out of fear and grumbling, and that the story of the reconciliation between the two poets is inaccurate, and the one who was condemned in the effort is Al-Atabi, and Al-Namri was not at first a hypocrite in his praise, because he was of the Kharijite school of thought, and after his conversion to Shiism his praise of Rashid became a dissimulation and dissimulation.